Paediatric snakebite envenoming: the world's most neglected 'Neglected Tropical Disease'?. Issue 12 (30th September 2020) - Pach, Sophie; Le Geyt, Jacqueline; Gutiérrez, José María; Williams, David; Maduwage, Kalana Prasad; Habib, Abdulrazaq Garba; Gustin, Rafael; Avila-Agüero, María Luisa; Ya, Kyaw Thu; Halbert, Jay
Abstract : Snakebite disproportionally affects children living in impoverished rural communities. The WHO has recently reinstated snakebites on its list of Neglected Tropical Diseases and launched a comprehensive Strategy for the Prevention and Control of Snakebite Envenoming. In the first of a two paper series, we describe the epidemiology, socioeconomic impact and key prevention strategies. We also explore current challenges and priorities including the production and distribution of safe and effective antivenom. Abstract : The first of a 2 part series highlights the global epidemiology of snakebite among children, disproportionately affecting children in rural areas of low and middle income countries. As with all Neglected Tropical Diseases, there is an inverse relationship between the local disease burden and resources available to prevent and manage snakebite.